Comunidades de la mesofauna edáfica en una selva baja inuudable de la Reserva de la Biósfera de Sian Kaan, Quintana Roo, Mexico - Prieto Trueba, Dania (1999)
The flood Jowland forest is a typical ecosystem of the Sian Kaan Biosphere in southeast Mexico. Two soi1 dwelling microarthropod samples were taken fram areas with different topographles, one in the dry season (March 1995) and one in the rainy season (July 1995). In ¡he rainy season, mean density was tbree times higher. Numerica11y, the Oribatid mites predominate, followed by Collembo1a and Pauropoda. regardless of the season or location. In March, the communities are concentrated in the soil, while the July sample showed a migration to the ¡eaf litter. There was no significant seasonal difference in densities. The propOltion Acarida: Collembo1a and the value of the Oreen Agregation Index for Collembola shows the marked effeet of dry soils for this group.